2021
DOI: 10.3390/vaccines9030249
|View full text |Cite
|
Sign up to set email alerts
|

Association between Venom Immunotherapy and Changes in Serum Protein—Peptide Patterns

Abstract: Venom immunotherapy (VIT) is administered to allergic patients to reduce the risk of dangerous systemic reactions following an insect sting. To better understand the mechanism of this treatment and its impact on the human organism, we analysed serum proteomic patterns obtained at five time-points from Hymenoptera-venom-allergic patients undergoing VIT. For statistical analyses, patients were additionally divided into two groups (high responders and low responders) according to serum sIgG4 levels. VIT was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
(83 reference statements)
1
4
0
Order By: Relevance
“…Here we observed a significant reduction in the blood concentration of C3 and C4 components, especially in the long period after desensitization with Hymenoptera venom, without any changes of the C5 concentration. These results are in agreement with Matysiak et al 39 , who showed decreased levels of C3 and C4 in serum of patients after venom immunotherapy (VIT) measured by MALDI-TOF MS technique. This may be a new mechanism by which desensitization modulates the immune 'system's response to Hymenoptera venom.…”
Section: Discussionsupporting
confidence: 93%
“…Here we observed a significant reduction in the blood concentration of C3 and C4 components, especially in the long period after desensitization with Hymenoptera venom, without any changes of the C5 concentration. These results are in agreement with Matysiak et al 39 , who showed decreased levels of C3 and C4 in serum of patients after venom immunotherapy (VIT) measured by MALDI-TOF MS technique. This may be a new mechanism by which desensitization modulates the immune 'system's response to Hymenoptera venom.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in the previous study performed by our team using the MALDI-TOF MS technique, we identified inflammation factors whose expression were altered in human serum under the influence of Hymenoptera venom immunotherapy [ 66 ]. The results of the abovementioned research indicate that most of the identified proteins change in serum after occasional stinging by insects and after venom-specific immunotherapy- Figure 5 .…”
Section: Searching For New Diagnostic Capabilities Of Hymen...mentioning
confidence: 99%
“…During VIT the number of effector cells in target organs also decreases, such as mast cells, basophils, innate type 2 lymphocytes, and eosinophils [54]. VIT was found to be associated with changes level of certain proteins i.e., fibrinogen alpha chain, complement C4-A, complement C3, filamin-B, kininogen-1, myosin-9 and inter-alphatrypsin inhibitor heavy chain H1 (Venom immunotherapy of patients leads to an increase in allergen-specific IgG, it shows clinical improvement of the patient after administration of antiserum.…”
Section: Discussionmentioning
confidence: 99%